1979
DOI: 10.1021/ja00505a042
|View full text |Cite
|
Sign up to set email alerts
|

Maleylacetone cis-trans-isomerase. Mechanism of the interaction of coenzyme glutathione and substrate maleylacetone in the presence and absence of enzyme

Abstract: Previous studies with maleylacetone cis-trans-isomerase suggest that the coenzyme, glutathione (GSH), may act as a nucleophile in the enzyme-catalyzed cis-trans isomerization. In the absence of enzyme, reaction of the coenzyme with maleylacetone or its trans isomer, fumarylacetone, has been found to lead to an adduct, S-2-(4,6-dioxoheptanoic acidjglutathione. The same diastereomer of the adduct is formed from either geometric isomer, suggesting that the reaction of GSH with maleylacetone proceeds by a slow cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

1979
1979
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 0 publications
1
25
0
2
Order By: Relevance
“…Therefore, a transferase reaction is not needed. After isomerization, free GSH and FAA are the products of the reaction (21,(33)(34)(35). MAA can bind GSH with or without enzyme and it has also been shown that GSH alone is able to catalyze the conversion of MAA to FAA in vitro (35).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Therefore, a transferase reaction is not needed. After isomerization, free GSH and FAA are the products of the reaction (21,(33)(34)(35). MAA can bind GSH with or without enzyme and it has also been shown that GSH alone is able to catalyze the conversion of MAA to FAA in vitro (35).…”
Section: Downloaded Frommentioning
confidence: 99%
“…However, MAAI is different in that glutathione binds to MAA spontaneously and the bound MAA-GSH is the substrate of the enzyme. After isomerization, free glutathione and FAA are the products of the reaction (Seltzer and Lin, 1979;Lee and Seltzer, 1989). MAAI binds glutathione, but does not transfer the substrate to the glutathione molecule.…”
Section: Structure and Mapping Of The Human Maleylacetoacetate Isomermentioning
confidence: 99%
“…There have been extensive studies in model systems closely related to this enzymic class (142,143,149,(153)(154)(155). Indeed, the cistrans isomerization of maleylacetone is catalyzed by the GSH coenzyme even in the absence of enzyme, but at a 106-fold lower rate (155).…”
Section: Maleyl Lsomerasesmentioning
confidence: 99%
“…Bond rotation about C-2-C-3 occurs more rapidly than protonation at C-3 (to explain the lack of solvent D uptake at C-2 or C-3 during reaction) (153). Thus the reaction of the cis isomer is isomerization while the trans isomer gives GSH addition (153).…”
Section: Maleyl Lsomerasesmentioning
confidence: 99%